UPAYA MENINGKATKAN HASIL BELAJAR LARI SPRINT MELALUI PERMAINAN HITAM-HIJAU PADA SISWA KELAS II SDN BULUSARI 1 KECAMATAN TAROKAN KABUPATEN KEDIRI TAHUN PELAJARAN 2024/2025” - Muhammad Khisbulloh; Wasis Himawanto; Dwi Sulistyo Nugroho (JURNAL ILMIAH NUSANTARA, 2025)
The main objective of incorporating physical activity and sports into education extends beyond enhancing physical fitness; it also aims to foster students' social and emotional development, overall health, critical thinking, mental toughness, and ethical conduct. This study focused on second-grade students at SDN Bulusari 1 during the second semester of the 2024/2025 academic year, involving a total of 32 participants. Data collection techniques included several methods such as tests, observations, interviews, and documentation. The results indicated a significant improvement in learning mastery, with 71% of students successfully meeting the achievement standards during the implementation of the first cycle—an indicator of progress in their sprinting skills. Considering the targeted achievement rate of 80%, the second cycle was considered successful and complete, as confirmed by ongoing observations and reflective evaluations. The average sprinting ability score of the students increased to 81.00, indicating that the implementation of the green-black game strategy was proven effective in enhancing their sprint performance.